Modyfikacje paremii „Na złodzieju czapka gore / На воре [и] шапка горит” w polskich i rosyjskojęzycznych mediach elektronicznych - Miturska-Bojanowska, Jolanta (Studia Rossica Posnaniensia, 2018)
The article discusses transformations of the proverb na złodzieju czapka gore / на воре [и] шапка горит in Polish and Russian-language online media (lexical changes, additions, grammatical modifications, contaminations).